Handbook of Research on Adult and Community Health Education Tools, Trends, and Methodologies - Wang, Victor C X (Medical Information Science Reference, 2015)
This book presents educational and social science perspectives on the state of the healthcare industry and the information technologies surrounding it, offering a compilation of some of the latest cutting edge research on methods, programs, and procedures practiced by health literate societies.